I costi di struttura dei servizi neurologici in Italia - Roggeri, Daniela; Garattini, Livio (Farmeconomia. Health Economics and Therapeutic Pathways, 2000)
The present study aimed to evaluate the mean unit cost of neurological services, broken down by type of output: hospital day of stay, day hospital day and outpatient consultation. The analysis concerned five neurological services (four hospital wards and one clinic), located in the North and Centre of Italy, selected among the 16 participants of the EPICOS (Epilepsy Costs) project. The most important result of this study was to estimate a baseline unit cost which can be used for assessing the total cost of a neurological disease. The study was conducted according to the full cost method. However, drugs and examinations were not included in this analysis, assuming that these costs are tightly related to the specific neurological pathology considered. Personnel was the most relevant component of total cost, accounting for 76% for outpatient services, 66% for admissions and 54% for day hospital. The estimated unit cost was L.395,000 for a hospital day of stay, L.527,000 for a day hospital day, and L.89,000 for an outpatient consultation.